Synergistic Effect of Moringa Leaf Extract (Moringa Oleifera Lam) and Purwoceng (Pimpinella alpine Molk) Supplementation on the Quality of Rural Chicken Semen - Heru Suripta; Puji Astuti (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2022)
This study was conducted to examine the synergistic effects of moringa oleifera and purwoceng (Pimpinella alpine molk) supplementation on the quality of chicken semen. In this study used roosters aged about 1 year weighing an average of 2.0 kg as much as 18 tails divided into 6 treatments, each 3 repeats, each repeat consists of 1 tail. The first group of chickens were used as controls, not given treatment, only given basal feed (T0). The second group of chickens were given moringa leaf extract as much as 1 gram / liter of drinking water (T1), chicken group 3 was given purwoceng extract as much as 1 gram / liter of drinking water (T2). Furthermore, chickens in group 4 (T3) were given moringa leaf extract supplements of 250 mg / liter of drinking water and 750 mg / liter per head per day and the 5th group (T4) were given moringa extract supplements as much as 500 mg / liter of drinking water and purwoceng 500 mg / L of drinking water ml every day (T5). The last group (T6) supplemented moringa leaf extract of 750 mg/L of drinking water and purwoceng of 250 mg/l of drinking water. Basal food in this study used BR-1 chicken feed produced by PT. Charoen Pokphand. As a pre-treatment adjustment the chicken is maintained 1 week with basal feed. Furthermore, chickens began to be treated by supplementation of moringa leaves, purwoceng and the mixture. On the 7th day after treatment, semen begins to be taken and tested. Semen collection is done every 3 days with the amount of 3 times the taking. The observed variables were semen volume per ejaculation, ejaculatory spermatozoa count (cells/ml), percentage of living sperm, motility, mass movement, color, viscosity and pH of semen. Results from semen volume and sperm count, motility and percentage of living sperm were analyzed with variance analysis using the spss series 25 program, while viscosity, color and pH were reported in a descriptive manner. From the results of observations it can be concluded that the synergistic effect between moringa leaf extract and purwoceng extract only occurs in the increase in the concentration of spermatozoa, but does not occur in other fractions. Supplementation of moringa leaf extract and its combination with purwoceng extract can increase the production and quality of chicken semen, but the influence of moringa leaf extract is more dominant than purwoceng extract. Keywords: Rural Chicken, Moringa oleifera, purwoceng (Pimpinella alpine Molk, semen quality